Institutional Structures and the Transformation of the Private Sector in Iraq - نصوري, فيصل اكرم; معن, حيدر حسن (Journal of Economics and Administrative Sciences, 2013)
Requires economic work finding built institutional paint strategies and policies are formulated general economic and clarity in its stated objectives and the involvement of all economic institutions, political and stakeholders to discuss all the issues of economic, financial, monetary and analyzed for the purpose of renewal energies and determine the duties and responsibilities, leaving full freedom to the private sector in the formation of institutions to carry out his duties economic, and that the institutional structures to create the right climate for the implementation of its economic policies, which would facilitate the task of the private sector, and this has been confirmed by the school institutional that institutional structures are appropriate framework that achieves a prerequisite for economic growth and development and is the school institutional structures function the natural evolution of society, authorized met with the views of politicians and economists, since you can not make economic reforms selective, ie does not fix economic institutions without reforming the political institutions of the state, so development must be comprehensive framework brings together all the institutional structures, where the word means (brown) a word structure Structure)) and signified linguistic word structures, that economic policies are a function expression for public policy of the state and trends determine the shape and economic system that a particular experience has shown beyond doubt, this vision, which can be seen clearly in the experience of Russia, which has followed a strategy (shock therapy), which was in accordance with the vision of the International Monetary Fund, which focused on the factors of production alone and do not cause changes similar institutional structures, while the experience of Bologna followed the alternative strategy (policy gradient) step by step in the transition to market mechanisms, are enabled to provide the institutional structures to be the solid ground that works to improve the effectiveness of the market economy